If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -250) + x = 0 Reorder the terms: (-250 + 2x) + x = 0 Remove parenthesis around (-250 + 2x) -250 + 2x + x = 0 Combine like terms: 2x + x = 3x -250 + 3x = 0 Solving -250 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '250' to each side of the equation. -250 + 250 + 3x = 0 + 250 Combine like terms: -250 + 250 = 0 0 + 3x = 0 + 250 3x = 0 + 250 Combine like terms: 0 + 250 = 250 3x = 250 Divide each side by '3'. x = 83.33333333 Simplifying x = 83.33333333
| 16w=256 | | 15+4g=-33 | | x+.08x=100 | | p^2-7p-30=0 | | 9x^2+30-29=0 | | 70=7+7+x+4+x+4 | | 9+9d=8d-12 | | 15+4g=33 | | 3x/23=2 | | =200+25+.02x | | 20x-7=-18-3 | | 3=-.018x^2+.25x-2.3 | | 2t^2+9t+7=0 | | 32+6x=44 | | 0=18x-9x^2 | | 66=3+n(5+4) | | 7-16-4= | | 12y-16=20 | | 66=3(5+4n) | | -3x(2x+5)=0 | | 6=8(s-75)-20 | | 5x^2+6x+5=32 | | 5x(5x)+6x+5=32 | | -8+15x+14=10x+12-8 | | (64x+8)-(10-3)= | | (12a^5-6a-10a^3)-(10a-2a^5-14a^4)= | | 64x+8=0 | | c^2+7c+18=0 | | (3-6n^5-8n^4)-(-6n^4-3n-8n^5)= | | 2x+5x+7+3x= | | 16=6z-20 | | (-4k^4+14+3k^2)+(-3k^4-14k^2-8)= |